Chronic and acute effects on skin temperature from a sport consisting of repetitive impacts from hitting a ball with the hands - Sánchez-Jiménez, J. L.; Tejero-Pastor, R.; Calzadillas-Valles, M. d. C.; Jimenez-Perez, I.; Cibrián Ortiz de Anda, R. M.; Salvador-Palmer, R.; Priego-Quesada, J. I. (Sensors, 2022)
Valencian handball consists in hitting the ball with the hands and it may contribute to injury development on the hands. This study aimed to analyze skin temperature asymmetries and recovery after a cold stress test (CST) in professional players of Valencian handball before and after a competition. Thirteen professional athletes and a control group of ten physically active participants were measured. For both groups, infrared images were taken at the baseline condition; later they underwent a thermal stress test (pressing for 2 min with the palm of the hand on a metal plate) and then recovery images were taken. In athletes, the images were also taken after their competition. Athletes at baseline condition presented lower temperatures (p < 0.05) in the dominant hand compared with the non-dominant hand. There were asymmetries in all regions after their match (p < 0.05). After CST, a higher recovery rate was found after the game. The regions with the most significant differences in variation, asymmetries and recovery patterns were the index, middle and ring fingers, and the palm of the dominant hand. Taking into account that lower temperatures and the absence of temperature variation may be the consequence of a vascular adaptation, thermography could be used as a method to prevent injuries in athletes from Valencian handball.